The International Criminal Court: Current Challenges and Perspectives - Hans-Peter Kaul (Washington University Global Studies Law Review, 2007)
In my view, all the members of the ICC, from the President to the most junior law clerk, continue to face some fundamental questions: How will we manage to turn the ICC into a functioning and effective institution? How will we cope with the limitations of this Court and with the challenges ahead? With these questions in mind, I would like to divide these remarks into two brief parts: First: Let me recall some of the legal, factual and other limitations which, also in the future, will have an impact on the work of the ICC. Second: In light of these limitations, what are current challenges and perspectives of the ICC?
Keywords: International Criminal Court; Jurisdiction (International law); International; International courts